2022
DOI: 10.1155/2022/6948934
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Internet Usage on Gender Division of Labour Bias: Evidence from Chinese General Social Survey Data

Abstract: Based on data from 18,741 respondents in the 2010 and 2017 Chinese General Social Survey, this paper empirically analyzes the influence of Internet usage on gender division of labour bias by using the propensity score matching model and tests the sensitivity of the estimated results. The results show that firstly, a series of personal characteristics such as gender, age, years of education, ethnicity, political status, health status, marital status, household registration status, labour income, mother’s years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…The dependent variables in this study are employment status and wage income. The principles for assigning employment status (es) and wage income (wi) are referenced from Gao and Liu (2022). Employment status is assigned a value of 1 if the female respondent's wage income is not equal to 0, otherwise it is assigned a value of 0.…”
Section: Dependent Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…The dependent variables in this study are employment status and wage income. The principles for assigning employment status (es) and wage income (wi) are referenced from Gao and Liu (2022). Employment status is assigned a value of 1 if the female respondent's wage income is not equal to 0, otherwise it is assigned a value of 0.…”
Section: Dependent Variablesmentioning
confidence: 99%
“…The independent variable in this study is internet technology usage (itu). The principle for assigning internet technology usage is referenced from Gao and Liu (2022). Internet technology usage is assigned a value of 1 when the female respondent frequently uses internet technology, otherwise it is assigned a value of 0.…”
Section: Dependent Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Control variables. Based on the reference of existing studies [Gao, 2021b;Liu et al, 2021;Gao and Liu, 2022] and the actual design of CGSS, this study combines age (Age, actual age of the respondent female), household registration status (HRS, respondent female's household registration status, rural household = 1, urban household = 0), marital status (MS, respondent female's marital status, married = 1, unmarried = 0), annual labor income (ALI, actual annual labor income of respondent females), and household investment activities (HIA, whether Цифровая социология / / Т. 6 , № 1 2023 г.…”
Section: Variable Settingsmentioning
confidence: 99%
“…In addition, it is also important to note that Chinese society has entered the digital era, and internet technology, as the underlying technology of various digital technologies, has profoundly changed the way of people's thinking and living [Gao, 2021a]. And some studies have shown that internetet usage can significantly improve Chinese females' gender competence perspectives and gender division of labour bias [Gao, 2021b;Gao and Liu, 2022]. It is worth considering whether the Internet intensifies or inhibits the spread of patriarchal culture, a factor that few studies have taken into account when studying patriarchal culture in current Chinese academia.…”
Section: Introductionmentioning
confidence: 99%